The role of sTNFSF14 in the liver mitochondrial dynamics in obese patients - A. A. Komar; D. A. Skuratovskaia; M. A. Vulf; H. Q. Vu; A. Darinskas; N. D. Gazatova; N. M. Todosenko; P. A. Zatolokin; E. V. Kirienkova; L. S. Litvinova (Бюллетень сибирской медицины)
Background. The pathogenesis of nonalcoholic fatty liver disease (NAFLD), which develops in obesity and type 2 diabetes mellitus (T2DM), is associated with the effects of inflammatory factors on the liver parenchyma and liver mitochondrial dysfunction.Aim. To determine the role of sTNFSF14 in the regulation of liver mitochondrial biogenesis in obese patients with and without T2DM.Materials and methods. The study included 263 obese patients with and without T2DM and 42 apparently healthy donors. Quantitative determination of cytokines in the blood plasma was performed by fluorescence flow cytometry. The level of relative gene expression in the liver biopsy samples was investigated by real-time PCR. Semi-quantitative determination of proteins in the liver biopsy samples was studied by western blotting.Results. The study showed that the levels of sTNFSF14, interleukin (IL)-10, gp130 / sIL-6Rb, and sIL-6Ra in the blood plasma of the obese patients without T2DM significantly exceeded the similar values in the control patients and obese patients with T2DM. In the liver biopsy samples of the obese patients with T2DM and a body mass index (BMI) > 40 kg / m2, the expression level of the dynamin-1-like protein (DRP1 / DNM1L) gene was lower than in the control group, and the expression level of the mitofusin 2 (MFN2) gene tended to be higher. Compared with the control group, an increase in the expression level of the NADH-ubiquinone oxidoreductase chain 4 (MT-ND4) gene was recorded in the liver of all the obese patients. The patients with obesity showed a decrease in the amount of mitochondrial DNA (mtDNA) compared with the control group.Conclusion. Thus, sTNFSF14, interacting with IL-10 and gp130 / sIL-6Rb in the circulation, positively effects the liver in the obese patients without T2DM. A low level of sTNFSF14 in the blood plasma of the obese patients with T2DM results in decreased mitochondrial division and increased cellular respiration.